Malnutrition in all its forms by wealth, education and ethnicity in Latin America: who are more affected?. (August 2020) - Batis, Carolina; Mazariegos, Mónica; Martorell, Reynaldo; Gil, Angel; Rivera, Juan A
Abstract: Objective: To summarise the findings from this supplemental issue on the distribution of malnutrition (stunting/short stature, anaemia and overweight) by wealth, education and ethnicity within and between ten Latin American countries. Design: We retrieved information from each country's article and estimated the average difference in the prevalence of malnutrition between groups. We estimated the associations between countries' malnutrition prevalence and GDP, percentage of women with high education and percentage of non-indigenous ethnicity. Setting: Nationally representative surveys from ten Latin American countries conducted between 2005 and 2017. Participants: Children (<5 years), adolescent women (11–19 years) and adult women (20–49 years). Results: Socially disadvantaged groups (low wealth, low education and indigenous ethnicity) had on average 15–21 (range across indicators and age groups) percentage points (pp) higher prevalence of stunting/short stature and 3–11 pp higher prevalence of anaemia. For overweight or obesity, adult women with low education had a 17 pp higher prevalence; differences were small among children <5 years, and results varied by country for adolescents by education, and for adults and adolescents by wealth and ethnicity. A moderate and strong correlation (–0·58 and –0·71) was only found between stunting/short stature prevalence and countries' GDP per capita and percentage of non-indigenous households. Conclusions: Overweight was equally distributed among children; findings were mixed for ethnicity and wealth, whereas education was a protective factor among adult women. There is an urgent need to address the deep inequalities in undernutrition and prevent the emerging inequalities in excess weight from developing further.